A produção textual de material didático para educação a distância - Silva, Luciene Santos Pereira da (2010)
Distance learning (ODL) has been seen by public universities as an important modality to promote the internalization and democratization of higher education. In this sense, the Federal Government has invested heavily in creation and maintenance of distance learning courses. In this development there are several aspects that need to be considered in offering a course in modality, among them we highlight the teaching resources to be available, in particular, the teaching material printed. In this sense, in this present research, carried out a study on the production of textual materials for distance education, focusing especially the teaching material printed once a there is a demand for the production of these institutions. Therefore, as a general objective is to offer subsidies to author teacher s that the help to make the text production of printed educational resource. Thus, were established the following specific objectives: to identify the author teacher s conception of language; the linguistic strategies used by them in textual production and verify the receptivity of a particular type of teaching material next to the students and identify the main demands of the students towards the material printed. The research was based on the analysis of teaching materials commonly used in distance learning courses, interviews, tests preference applied with students, author teachers and pedagogical coordination of courses in ODL of Universidade Federal Rural de Pernambuco. The work includes, above all, the textual linguistics and the prospects sociointeractionists and sociocognitivist as a theoretical basis. At the end of the research, some possibilities are indicated for the elaboration of texts appropriate to the modality. The results achieved can expand our studies in language, in line with the issues linked to the technological context